2009
DOI: 10.1155/2010/979675
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antimicrobial Activity of Quinazolinone Conjugated Peptides

Abstract: Antimicrobial compounds were synthesized by coupling 4-(4-oxo-3,4-dihydroquinazolin-2-yl) butanoic acid with VP, GVP, VGVP and GVGVP peptides. Antimicrobial activities of the synthesized compounds were performed against various bacterial strains by disc diffusion method. The structure activity relationship was evaluated with respect to hydrophobicity, polarity, chain length of peptides and alkyl chain length of quinazolinone. Correlations of analogs with respect to their antimicrobial activity in comparison wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…enthusiastically embarrassed mass spectroscopy to identify and characterize molecule Mass spectrum of the compound is a plot which represents the intensities of the signals at various m/z value [42][43] . It is highly characteristic of the compound ,no two compounds can have similar mass spectra.…”
Section: Mass Spectrum Of Glz-au Complexmentioning
confidence: 99%
“…enthusiastically embarrassed mass spectroscopy to identify and characterize molecule Mass spectrum of the compound is a plot which represents the intensities of the signals at various m/z value [42][43] . It is highly characteristic of the compound ,no two compounds can have similar mass spectra.…”
Section: Mass Spectrum Of Glz-au Complexmentioning
confidence: 99%
“…The peptides alone were the least hydrophobic and inactive towards the bacterial strains, but an enhanced activity even greater than that of the commercial drug was reported when the peptides were conjugated with the heterocyclic compound. It was also observed that an increase in the length of the peptide chain, variation in polarity and hydrophobicity of the molecules were responsible for increased antimicrobial activity [ 116 ].…”
Section: Conjugated or Hybrid Moleculesmentioning
confidence: 99%
“…Substituted 4(3H) quinazolinones possess a wide rang of pharmacological activities such as antimicrobial [1,2], anticancer [3], antiviral [4], anti-inflammatory [5], antitubercular [6], antitumor [7], antioxidant [8] and anticonvulsant [9].…”
Section: Introductionmentioning
confidence: 99%